Pengaruh Kepuasan Kerja dan Stress Kerja Terhadap Kinerja Karyawan PT. Mekar Karya Mas - Frizkha Hariana (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2021)
This study aims to analyze the effects of job satisfaction and job stress on the performance of PT Mekar Karya Mas employees either partially or simultaneously. This study used an explanatory research approach. The population in this study were all employees at PT. Mekar Karya Mas is as many as 65 people and the sample in this research is 61 people. The types of data used are primary data and secondary data, the instruments (tools) for collecting research data used are questionnaires and interviews. To produce good data, validity and reliability tests were carried out. The data analysis technique is multiple linear regression analysis. Partially, each variable job satisfaction and job stress affect employee performance. Simultaneously, the variables of job satisfaction and job stress have an effect on the performance of employees of PT Mekar Karya Mas.